A Facile Potential Hold Method for Fostering an Inorganic Solid‐Electrolyte Interphase for Anode‐Free Lithium‐Metal Batteries. Issue 13 (9th February 2022) - Shin, Woochul; Manthiram, Arumugam
Abstract: Anode‐free lithium batteries are regarded as an ultimate form of high‐energy‐density lithium‐ion batteries. Unfortunately, irreversible lithium loss during cycling plays a major role in degrading the overall cell performance in the anode‐free configuration. To alleviate the deterioration, building a robust solid‐electrolyte interface on an anode current collector is an indispensable requirement. Here, we present a facile in‐situ electrochemical method of a potential hold during the first charge to guide more salt‐derived (less solvent‐derived) decomposition on the anode interface. We show the distinctive decomposition potential of lithium salts and ether/carbonate solvents, where the Li‐solvation structures with salt contact‐ion‐pairs preferentially decompose to form LiF‐rich and less organic components, leading to enhanced lithium Coulombic efficiency in Li||Cu cells as well as mitigating the capacity fade of Cu||LiFePO4 and Cu||LiNi0.8 Mn0.1 Co0.1 O2 cells. Abstract : A facile potential hold process fosters the growth of a more inorganic solid‐electrolyte interphase (SEI) for anode‐free lithium‐metal batteries. Owing to the various decomposition potentials of the Li‐solvation structures, salt anion‐derived SEI was preferentially established on the current collector while reducing the components from organic solvents.